Low-energy activation of large convective heat transfer via flow resonance triggered by impinging jet. (October 2022) - Torres, Juan F.; Ogasawara, Naoto; Koizumi, Takuma; Kanda, Yuki; Komiya, Atsuki
Highlights: Flow instability in mixed convection triggers large convective energy transfer. Moderate jets can enhance heat transfer more than tenfold compared to stronger jets. Flow resonance significantly amplifies the thermal energy transfer. Optical diagnosis of thermal boundary layer unveils mechanism of large enhancement. Abstract: Cooling performance by natural convection is generally enhanced by increasing the surface area using fin arrays, but their implementation is problematic in large surfaces such as a building facade. We recently reported a phenomenon whereby flow resonance triggered by an impinging jet can enhance convective heat transfer without the need of increased surface area. Here, we propose and investigate the concept of a low-energy activation method (i.e. using moderate jets) based on flow resonance for convective heat transfer enhancement over extensive surfaces. We focus on varying the impinging location y imp near the leading edge of the heated plate (local Rayleigh number of R a y ≤ 5 × 10 7 or y imp ≤ 300 mm), the momentum of the impinging planar jet (Reynolds number of R e ≤ 400 ), and the net buoyancy of the thermal boundary layer (global Rayleigh number of R a ≤ 1.12 × 10 11, i.e. ≤ 4 m vertical walls heated at 316 K). Instability waves were observed downstream over the heated surface via simulations (computational fluid dynamics) and experiments (large-aperture interferometry), resulting in a downstream heat transfer enhancement compared to that of pure natural convection of about 40% to 60% depending on the impinging position for plates shorter than 1 m. However, turbulent convective heat transfer was reduced from the natural convection case at high R a y . As a means of introducing flow resonance in the thermal boundary layer, we demonstrate that the frequency of the oscillating flow in the mixed convection region can be tuned by selecting appropriate Reynolds number and impinging position of the jet. A combination of flow resonance generation (downstream) and boundary layer thinning around the impinging region (upstream) yields a low-energy activation method for enhancing convective heating and cooling performance.